BUSINESS AND MANAGEMENT TEACHERS' PERCEPTION OF THE INDEPENDENT LEARNING CURRICULUM AT STATE VOCATIONAL SCHOOL 1 SIGLI, PIDIE DISTRICT - Ayu Putri; Darmi Darmi; Maisura Maisura (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2026)
ABSTRACTThe study entitled "Perceptions of Business and Management Teachers of the Independent Learning Curriculum at SMK Negeri 1 Sigli, Pidie Regency" aims to describe teachers' perceptions of the implementation of the Independent Learning Curriculum and identify factors that influence these perceptions. The method used is descriptive qualitative with a post-positivism approach, by collecting data through observation, interviews, and documentation, and form of analysis technique, namely the interactive model. The research subjects were Business and Management expertise program teachers consisting of 7 (Seven) fields including; Accounting and Finance Institutions (AKL), Office Management and Business Services (MPLB / OOTKP), Marketing (PMS), Hospitality (PMS), Hospitality (PMS), and Hospitality (PMS). (PMS), Hospitality (PHT) or Hospitality and Tourism Services (PJP), Culinary (KLN), Beauty and Spa (BCE), and Beauty and Spa (BCE).(KLN), Beauty and Spa (KS), and Fashion (BSN). The results showed positive (Good) teacher perceptions of this curriculum, influenced by internal factors (knowledge, motivation, attitudes, and confidence) and external factors (school support and learning environment) This study recommends increasing teacher knowledge and institutional support and collaboration with industry, can be continued by other researchers from variouslevels of education so that it can reveal things that have not been revealed. Keywords: Teacher Perception, Merdeka Belajar Curriculum, SMK, Business and Management.